SPIRITUAL VALUES IN PRE-ISLAMIC ARABIC LITERATURE - Huwaida (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2022)
Poetry is an accumulation of beauty and imagination in the form of compositions that represent the subtlety of feelings and have messages that penetrate the recesses of the soul. Although the poetry comes from a time when there was not yet has a light of divine truth, there has been poetry with spiritual values touching the spiritual experiences. Therefore, this study aims to examine poetry that has spiritual value in pre-Islamic Arabic literature. Content-analysis is applied to find the spiritual values in a selected poetry. The result shows that spiritual values emerged such as kindness and compassion for others; generosity; deep thoughts about death; peacefulness; keeping promise; sincerity.